발달 독성학에서 비대칭 로짓 모형을 사용한 이진수 자료와 연속형 자료에 대한 결합분석 - 김영화; Yeong-hwa Kima; 황범석; Beom Seuk Hwanga (Ŭngyong tʻonggye yŏnʼgu, 2020)
하나의 개체에서 여러가지 측정치가 동시에 관찰되는 경우는 다양한 연구 분야에서 흔히 나타난다. 발달 독성학 연구에서는 특정 독성 물질의 각기 다른 수준에 노출된 임신한 어미 쥐에 대해 기형인 태아의 존재와 태아의 무게가 동시에 측정된다. 이런 두 변수를 결합하여 모형화하는 것은 각기 독립적인 두 모형으로 분석하는 것보다 더 효율적인 결과를 낸다고 알려져 있다. 대부분의 결합 모형은 정규분포를 랜덤효과로 가정하여 분석한다. 그러나 발달 독성학연구에서처럼 반응변수들의 분포가 독성 물질이 변함에 따라 불규칙하게 변하는 경우 정규분포의 가정으로는 그 특징을 잡아낼 수 없게 된다. 본 논문에서는 이진수 자료와 연속형 자료에 대해 비대칭 로짓 모형을 사용한 베이지안 결합모형을 제시한다. 본 모형은 비대칭 로짓 모형을 사용함으로써 반응변수의 분포의 형태가 독성 물질의 수준에 따라 대칭/비대칭의 형태를 자유롭게 띨 수 있는 장점을 가지고 있다. 모형의 적합성을 살펴보기 위해 발달 독성학연구에서 독성 물질 DEHP에 적용하여 그 결과를 확인해본다. It is common to encounter correlated multiple outcomes measured on the same subject in various research fields. In developmental toxicity studies, presence of malformed pups and fetal weight are measured on the pregnant dams exposed to different levels of a toxic substance. Joint analysis of such two outcomes can result in more efficient inferences than separate models for each outcome. Most methods for joint modeling assume a normal distribution as random effects. However, in developmental toxicity studies, the response distributions may change irregularly in location and shape as the level of toxic substance changes, which may not be captured by a normal random effects model. Motivated by applications in developmental toxicity studies, we propose a Bayesian joint model for binary and continuous outcomes. In our model, we incorporate a skewed logit model for the binary outcome to allow the response distributions to have flexibly in both symmetric and asymmetric shapes on the toxic levels. We apply our proposed method to data from a developmental toxicity study of diethylhexyl phthalate.